2019
DOI: 10.1111/1556-4029.14052
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study on Vacuum Metal Deposition as a Standalone Method for Enhancement of Fingermarks on Ballistic Brass Materials

Abstract: In order to assess the efficacy of vacuum metal deposition (VMD) as a technique to develop fingermarks on ballistic metallic surfaces, a preliminary study using six donors (three male & three female) was conducted. Using a sequential metal deposition process, two metal combinations were studied—gold/zinc and silver/zinc. Results indicate the potential of this technique, by developing identifiable fingermarks on brass metal disks aged from a few days up to more than a month old. As the development of fingermark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Therefore, the fingermarks of donors who produce large quantities of these components may not develop effectively thus producing the poor-quality marks. Their study also exposed marks to a higher vacuum and a longer time than during a VMD treatment, meaning that vacuum effects in our study may not be as prevalent [20,23].…”
Section: Aged Marksmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, the fingermarks of donors who produce large quantities of these components may not develop effectively thus producing the poor-quality marks. Their study also exposed marks to a higher vacuum and a longer time than during a VMD treatment, meaning that vacuum effects in our study may not be as prevalent [20,23].…”
Section: Aged Marksmentioning
confidence: 96%
“…VMD involves evaporation and deposition of a variety of metals, most commonly gold or silver, followed by zinc, within a high vacuum chamber [20]. The initial metal forms a thin film across the entire surface made up of small clusters of the metal atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other sections – The following papers are detailed in other sections of this report: ability of VMD to detect fingermarks on brass plates and fired cartridge cases [ [267] , [268] , [269] , [270] , [271] ] – See Section 4.4.4 ; performance of the sequential processing involving VMD and amino acid reagents on thermal papers [ 272 ] – See Section 4.4.5 ; impact of corrosive substances on fingermark recovery [ 273 ] – See Section 4.5.3 .…”
Section: Fingermark Visualisationmentioning
confidence: 99%
“…VMD – A series of preliminary studies (few donors and/or sebum-rich fingermarks) investigated the ability of VMD to be applied on brass plates and fired cartridge cases [ [267] , [268] , [269] , [270] , [271] ]. Given their preliminary nature, all these studies require further experiments to strengthen their conclusions, which were the following: positive results were obtained with VMD Au/Zn and VMD Ag/Zn [ 268 , 270 ], both studies emphasizing the influence of the donor and the detrimental impact of the firing event. In her comparative studies, Brewer concluded that VMD Al suited best brass rifle cartridge casings [ 267 ], VMD Au/Zn – wad shotgun cartridges [ 267 ], and VMD Ag – brass handgun casings [ 269 ].…”
Section: Fingermark Visualisationmentioning
confidence: 99%